Historical development and use of the American College Testing Program in establishing admissions requirements at the University of Wisconsin - La Crosse - Wendel, Diane (My University, 1987)
The purpose of this research was to provide a historical account of the development of the American College Testing Program (ACT) and to examine the use of the ACT Assessment in establishing admissions requirements to UWL. The ACT was founded in 1959 but it would not be until 1966 that the Board of Regents required the test for entrance into the Wisconsin State Universities. The ACT was established as an entrance requirement rather than an admissions requirement and was used mainly for research purposes in its early years. In 1974 the ACT assessment was no longer required for entrance at UWL but was reinstated in 1976. In recent years, there has been concern among admissions officers that enrollment in colleges and universities would be adversely affected by a continuing decline in the 18-year-old population. Despite this trend, UWL is faced with increasing enrollments. Concern that students be provided with a quality education has led to implementation of new enrollment management plans in the UW System beginning in 1991 and at UWL in 1988. It was hoped that information obtained would provide a clearer understanding of the role of the ACT in enrollment management. The research consisted of a literature review focusing on the historical development of entrance examination, personal interviews, and related university documents. Recommendations were made for the use of the ACT Assessment in admissions and for further study of this topic.
Keywords: University of Wisconsin--La Crosse -- Admission; ACT Assessment